Impacto de las Estrategias de Campaña de Daniel Noboa en la Opinión Pública durante las Elecciones Presidenciales en Loja, Ecuador en 2023 - Garrido Cumbicos, Verónica Francisca (2024)
Impact of Daniel Noboa's Campaign Strategies on Public Opinion during the Presidential Elections in Loja, Ecuador in 2023 The study "Impact of Daniel Noboa's Campaign Strategies on Public Opinion during the Presidential Elections in Loja, Ecuador in 2023" looks at how these tactics work in a highly competitive electoral environment. A candidate's ability to control their perceptions and image is crucial in swaying the electorate. Using a mixed technique, this study offers a view of the phenomenon by combining qualitative and quantitative analyses. To gather public opinion before, during, and after the campaign, surveys were conducted among Loja residents. A content analysis of the media, both digital and traditional, was also carried out to evaluate the media representation of Noboa's strategies. The study encompassed interviews with political communication specialists and an examination of the candidate's social media activity. The primary findings indicate that the campaign tactics, specifically the emphasis on regional concerns and the proactive engagement on digital channels, significantly influenced the public's viewpoint of Noboa. Science and society can both benefit from this research. Within the academic community, it offers insight into how public opinion can be influenced by campaign tactics in comparable situations, providing a template that can be used in future elections. For society, it offers practical recommendations for the planning and execution of electoral campaigns, and thus contribute more effectively to political communication and a better representation of the needs and concerns of the electorate. Keys words: campaign strategies, public opinion, presidential elections